Determinants of Employees’ Work Ethic - Vitaloka, Rica Andria; Eliza, Yulina; Sumiati, Sumiati (ADPEBI Publisher, 2026)
This study aims to examine the effect of work experience, work environment, and work discipline on the work ethic of employees at the District Head Office of Kumun Debai Subdistrict, Sungai Penuh City. A quantitative research approach was employed, involving 33 respondents as the research sample. Data were collected through questionnaires and analyzed using IBM SPSS version 25. The analysis procedure included validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The results indicate that work experience, work environment, and work discipline simultaneously have a significant effect on employees’ work ethic. Partially, work experience and work environment show a positive and significant influence on work ethic, while work discipline does not have a significant effect. These findings suggest that employees’ work ethic is more strongly shaped by adequate work experience and a supportive work environment than by work discipline that is predominantly administrative in nature. This study highlights the importance of enhancing work experience through continuous training and development, as well as creating a conducive work environment, as strategic efforts to improve employees’ work ethic and the quality of public services within local government institutions.